Financial openness, policy vs. realized outcomes - Georgia Ramsay Bush (Banco de México, 2018)
This paper examines how the 1990s capital account liberalization policy trend affected international capital flows, and tests a new hypothesis that the depth and efficiency of the domestic financial system impacts the efficacy of capital account policy. The paper exploits a recently published IMF database on financial development that spans the period 1980-2014 and includes both developing and developed countries. The results confirm that policy on average does not have a significant effect on gross capital flows, when controlling for other factors. I also find no effect on flows disaggregated by type and direction. However, interacting capital account policy and financial development, I do find that for financially developed countries, policy has the expected effect - policy openness leads to capital flows. The implication is that the effectiveness of capital account liberalization requires developing the domestic financial system.
Keywords: F3; F4; 330; financial globalization; financial integration; financial development; capital flows; capital control measures